ERP components in Go/Nogo tasks and their relation to inhibition - Falkenstein, M; Hoormann, J; Hohnsbein, J (Acta psychologica, 1999)
In visual Go/Nogo tasks the ERP usually shows a frontal negativity after Nogo stimuli (“Nogo-N2”), which possibly reflects an inhibition process. However, the Nogo-N2 appears to be very small after auditory stimuli, which is evidence against the inhibition hypothesis. In the present study we tested this hypothesis by evaluating performance differences between subjects. Assuming that for Ss with a high false alarm rate the inhibition process is weakened and/or delayed, they should reveal a smaller and/or later Nogo-N2 than Ss with a low false alarm rate. This prediction was confirmed, which supports the inhibition hypothesis. However, the Nogo-N2 was again much smaller and had a different topography after auditory than after visual stimuli despite similar performance in both modalities. This modality asymmetry was explained by assuming that the inhibitory mechanism reflected in the Nogo-N2 is located at a pre-motor rather than at the motor level. In the second part of the study we compared the Nogo-N2 with a similar phenomenon, the error negativity ( N e), which occurs in trials with commission errors (false alarms). Earlier work suggests that the N e is a correlate of error detection or inhibition. This raises the possibility that the N e is a delayed Nogo-N2, i.e., the N e may reflect a late and hence unsuccessful attempt to inhibit the response after a nontarget. However, the N e amplitude showed no difference between performance groups and stimulus modalities, as found for the Nogo-N2. Moreover, N e and Nogo-N2 had different scalp topographies. This suggests that different mechanisms and generators underlie the N e and the Nogo-N2.